Numerical solution of singularly perturbed two parameter problems using exponential splines - Padmaja, Poosapati; Aparna, Podila; Gorla, Rama Subba Reddy; Pothanna, N. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we have studied a method based on exponential splines for numerical solution of singularly perturbed two parameter boundary value problems. The boundary value problem is solved on a Shishkin mesh by using exponential splines. Numerical results are tabulated for different values of the perturbation parameters. From the numerical results, it is found that the method approximates the exact solution very well.
Keywords: singular perturbation; convection-diffusion problem; exponential splines; numerical convergence